Comparison of Induction Cooker Power Converters - Ozturk, Metin; Aslan, Sezer; Altintas, Nihan; Sinirlioglu, Sercan (IEEE, 2018)
Due to user safety, efficient heating, easy cleaning, fast heating, and smart design reasons, induction heating technology is very popular in home appliances. The technical developments for the induction technology can be seen in magnetic design, power electronic, and control techniques. These technical developments focus on developing induction heating futures without increase total system cost. In this study, it is aimed to analyze the existing converters which are using for induction cooking and compare them in terms of losses and efficiency. Conventional and AC-AC converters have been analyzed and compared for the single load and double loads conditions. Efficiency, semi-conductor quantity, total system cost, and control flexibility are main topics for comparison.
Keywords: AC-AC converter; multiple coil; induction cooking systems; resonant converters; home appliances; induction cookers; single ended converters; halfbridge converter; Automation & Control Systems; Computer Science; Engineering